The Effect of Eye Movement Desensitization and Reprocessing on Pain Intensity in Cancer Patients (24-Month Follow-Up) - A Mansoorian; P Zaj; N Abdi; H Hejr; M Alizadeh; GH Sabz; J Pouranfard (Armaghane Danesh Bimonthly Journal, 2022)
Background & aim: Managing pain and mental distress in cancer patients is one of the main priorities of care. Therefore, the aim of the present study was to determine and evaluate the effect of desensitization with eye movements and reprocessing on pain intensity in cancer patients with 24-month follow-up.